Актуальність використання принципів архітектурної типології спілки Ф. Фельнера і Г. Гельмера для швидкої відбудови промислових об’єктів України після війни з РФ - Іванов-Костецький, Сергій; Проскуряков, Олексій; Пиндзин, Мар’ян; Ivanov-Kostetsky, Serhii; Proskuriakov, Oleksii; Pyndzyn, Marian (Видавництво Львівської політехніки, 2022)
У статті висвітлено принципи формування архітектури будівель і споруд спілки архітекторів Ф. Фельнера і Г. Гельмера і, зокрема, типів, використання яких є актуальним для швидкої відбудови промислових об’єктів в умовах сучасної України після війни з рф.

The article highlights the formation principles of architecture of buildings and structures of the union of architects F. Fellner and G. Helmer and, in particular, the types of use which are relevant for the rapid reconstruction of industrial facilities in modern Ukraine after the war with Russia. The most important principles that have been tested over time and could be implemented in the reality of rebuilding the architecture and environment of the destroyed Ukrainian territories are: design taking into account the prospects of the time; predominance of functionality criteria; the use of solutions on the border of functions and, in particular, in the construction of industrial architecture.
The urgency of using the architectural typology principles of the union of F. fellner and G. helmer for the rapid reconstruction of industrial facilities in Ukraine after the war with Russia
Keywords: класифікація будівель і споруд Ф. Фельнера і Г. Гельмера; розвиток принципів; рекомендації та використання актуальних типів промислових будівель; повоєнне проєктування і будівництво в Україні; classification of buildings and structures by F. Fellner and G. Helmer; development of principles; recommendations for current types of industrial buildings; post-war design and construction; 7256711.168(477)